Preparation and photocatalytic activities of Au-Fe2O3 hybrid nanoparticles - Chen, Hu. (2012)
This report serves as a comprehensive summary of the 10-month research experience with Solar Fuel Lab, Nanyang Technological University. In this project, Fe2O3 nanoparticles with different morphologies and Au-Fe2O3 hybrid nanoparticles were prepared and photocatalytic degradation of Methyl Orange catalysed by these nanoparticles was investigated. The first part was the synthesis of the nanoparticle samples. For Fe2O3, three sample solutions were prepared by mixing of Fe(NO3)3∙9H2O and CO(NH2)2. Then a tiny amount of ethanolamine, polyvinylpyrrolidone, or sodium dodecyl sulphate was added into the three samples respectively to obtain different morphologies. For Au-Fe2O3, the sample prepared by PVP (polyvinylpyrrolidone, k value = 29-32) was selected for Au-Fe2O3 fabrication since this sample has the best photocatalytic performance. The second stage was the investigation on photocatalytic activities of the prepared samples. 5mg sample was dissolved in 10mL Methyl Orange with concentration of 5mg/L, which was then irradiated by a Xenon lamp (MAX 150W) for 4 hours; during the irradiation, 1.25mL sample was taken every 60 minutes for concentration detection. The photocatalytic experiment result revealed that Fe2O3 nanoparticles are efficient photocatalysts, while the morphology has an effect on the efficiency. Besides, comparison between photocatalytic efficiency of Fe2O3 nanoparticle and Au-Fe2O3 hybrid nanoparticle showed that gold nanoparticle can improve the photocatalytic efficiency.